Increased galectin-1 expression in muscle of Astragalus polysaccharide-treated Type 1 diabetic mice - Zhou, Xingjian; Xu, Yancheng; Yang, Guoming; Li, Fang (Journal of natural medicines, 2011)
In order to investigate the immunopharmacological function of Astragalus polysaccharide (APS) in Type 1 diabetes mellitus (T1DM), multiple low-dose streptozotocin-induced diabetic mice and normal mice were administered either APS or saline intraperitoneally once daily. The changes in galectin-1 expression in different organs of the mice were detected by ELISA, Real-time fluorescence quantitative RT-PCR and Western blot. The percentages of apoptotic CD8 + T cells from spleens of APS-treated diabetic mice were measured by flow cytometry. We found that the expression of galectin-1 was increased in serum of APS-treated diabetic mice compared to the non-treated diabetic mice (* p < 0.05). Increased galectin-1 was mainly expressed in the muscle of APS-treated mice. In vitro, APS up-regulated the expression of galectin-1 in muscle cells in a dose-dependent manner. The percentage of apoptotic CD8 + T cells in spleens of APS-treated mice was positively correlated with the concentration of APS treatment, and the blocking of galectin-1 in vivo by specific antibody reduced the percentage of apoptotic CD8 + T cells in APS-treated mice. Our findings indicated that APS could up-regulate the expression of galectin-1 in muscle of T1DM mice, resulting in the apoptosis of CD8 + T cells. This may be an important mechanism by which APS protects β cells of the pancreatic islets from apoptosis induced by CD8 + T cells in T1DM in vivo.